2016
DOI: 10.5137/1019-5149.jtn.17711-16.1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of early rehabilitation after surgical repair of acute aneurysmal subarachnoid hemorrhage: outcomes after verticalization on day 2-5 versus day 12 post-bleeding

Abstract: AIm: To develop a specific rehabilitation protocol for patients who have undergone surgical repair of acute aneurysmal subarachnoid hemorrhage (aSAH), and to determine the time at which verticalization should be initiated after aSAH. mATERIAl and mEThODS: Sixty-five patients who underwent acute-term surgery for aSAH and early rehabilitation were evaluated in groups: Group 1 (n=34) started verticalization on days 2-5 post-bleeding whereas Group 2 (n=31) started verticalization approximately day 12 post-bleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Based on these mechanisms and MFS, modified Fisher scale; HR, hazard ratio; CI, confidence interval; aSAH, aneurysmal subarachnoid hemorrhage evidence, our results suggest that initiating mobilization within 7 days after onset was not associated with SCV. In contrast, early mobilization initiated 2-5 days after onset was found to be the cause of cerebral vasospasm and delayed cerebral ischemia 20) . This previous study compared the early mobilization group (mobilization initiated 2-5 days after onset) with the non-early mobilization group (mobilization initiated after 12 days after onset), whereas this study compared the early mobilization group (mobilization initiated within 7 days after onset) with the non-early group (mobilization initiated after 7 days after onset).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Based on these mechanisms and MFS, modified Fisher scale; HR, hazard ratio; CI, confidence interval; aSAH, aneurysmal subarachnoid hemorrhage evidence, our results suggest that initiating mobilization within 7 days after onset was not associated with SCV. In contrast, early mobilization initiated 2-5 days after onset was found to be the cause of cerebral vasospasm and delayed cerebral ischemia 20) . This previous study compared the early mobilization group (mobilization initiated 2-5 days after onset) with the non-early mobilization group (mobilization initiated after 12 days after onset), whereas this study compared the early mobilization group (mobilization initiated within 7 days after onset) with the non-early group (mobilization initiated after 7 days after onset).…”
Section: Discussionmentioning
confidence: 91%
“…A previous study suggested that early mobilization did not increase the incidence of SCV 19) . In contrast, another study found that early mobilization initiated 2-5 days after onset was caused by delayed cerebral ischemia 20) . Mobilization may increase intracranial pressure and decrease cerebral perfusion pressure, which may exacerbate cerebral vasospasm and delayed cerebral ischemia 21,22) .…”
mentioning
confidence: 94%
“…The greater the damage, the longer the operation, the more interleukin-6 is released, the more stress develops in response [5]. A larger incision causes more pain and prevents early verticalization, which is a very important factor in the patient's recovery, return to normal functioning and reduction of postoperative complications [12]. Also, the restoration of oral nutrition minimizes the effect of stress diabetes, which is a leading factor in the healing of surgical wounds, the development of infectious postoperative complications [1,19].…”
Section: Discussionmentioning
confidence: 99%
“…The technique of simultaneous laparoscopic interventions has many opportunities for development, because comorbidity in surgical patients is not uncommon. The most common combinations of surgical pathologies within the abdominal cavity are cholecystolithiasis and diaphragmatic esophageal hernia, cholecystolithiasis and inguinal hernia, cholecystolithiasis and liver tumors, cholecystolithiasis and kidney tumors [12]. Therefore, the implementation of simultaneous surgical treatment for these groups of patients is promising.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns regarding changes in intracranial pressure and cerebral perfusion pressure due to early mobilization and their impact on the development of cerebral vasospasm and ischemia have been raised (6). In a randomized controlled study, cerebral ischemia and motor paralysis were increased when early mobilization was initiated within 2-5 days of onset (47). However, other studies have reported a decrease in SCV or no association with early mobilization (30,45).…”
Section: Several Factors May Explain the Association Between Walking ...mentioning
confidence: 94%